2019
DOI: 10.1038/s41436-019-0448-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NUDT15 genetics on severe thiopurine-related hematotoxicity in patients with European ancestry

Abstract: PurposeSevere hematotoxicity in patients with thiopurine therapy has been associated with genetic polymorphisms in the thiopurine S-methyltransferase (TPMT). While TPMT genetic testing is clinically implemented for dose individualization, alterations in the nudix hydrolase 15 (NUDT15) emerged as independent determinant of thiopurine-related hematotoxicity. Because data for European patients are limited, we investigated the relevance of NUDT15 in Europeans.MethodsAdditionally to TPMT phenotyping/genotyping, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 17 publications
4
58
1
1
Order By: Relevance
“…With the development of genomic technology, novel and an ethnic-specific pharmacogenetic marker in NUDT15 (i.e., rs116855232) has been identified through genome-wide association studies (Yang et al, 2015;Moriyama et al, 2016) and validated by multiple independent studies. Allele frequency of rs116855232 is approximately 10% in East Asians, accounting for a large proportion of 6MP-induced leukopenia, as well as 6MP tolerance with high sensitivity and specificity in such population (Yin et al, 2017;Zhu et al, 2018;Relling et al, 2019;Schaeffeler et al, 2019). Ethnic specificity is observed for rs116855232, because allele of this variant is close to 0% in Caucasians and Africans, which is much lower than that in East Asians.…”
Section: Introductionmentioning
confidence: 95%
“…With the development of genomic technology, novel and an ethnic-specific pharmacogenetic marker in NUDT15 (i.e., rs116855232) has been identified through genome-wide association studies (Yang et al, 2015;Moriyama et al, 2016) and validated by multiple independent studies. Allele frequency of rs116855232 is approximately 10% in East Asians, accounting for a large proportion of 6MP-induced leukopenia, as well as 6MP tolerance with high sensitivity and specificity in such population (Yin et al, 2017;Zhu et al, 2018;Relling et al, 2019;Schaeffeler et al, 2019). Ethnic specificity is observed for rs116855232, because allele of this variant is close to 0% in Caucasians and Africans, which is much lower than that in East Asians.…”
Section: Introductionmentioning
confidence: 95%
“…From a cost and benefit perspective, it might be difficult to use cDNA NGS to determine the diplotype of NUDT15 in clinical practice; moreover, the incidence of compound heterozygous mutations, such as NUDT15 *3/*6, is very rare 18 . Sanger sequencing remains the most convenient and cost-effective method for the analysis of genetic variants of NUDT15 17 , 18 , 20 , 25 , 27 , 28 , 31 , 32 , 35 . However, to improve clinical outcomes and reduce adverse effects in pediatric patients with ALL, appropriate preemptive diagnosis of pharmacogenetic variants might be warranted 31 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in many recent studies, NUDT15 gene defects (rs116855232, rs186364861, rs869320766, rs201094029) have shown to result in increased TG availability for incorporation into DNA and have consistently been associated with TG toxicity including early myelosuppression (Chiengthong et al, 2016;Moriyama et al, 2016;Lee and Yang, 2017;Soler et al, 2018;Choi et al, 2019;Khera et al, 2019;Koutsilieri et al, 2019). The incidence of NUDT15 gene defects is higher in Asian and Hispanic populations, but NUDT15 genetic polymorphism has also been described in European patients (Schaeffeler et al, 2019). Therefore, the most recent CPIC guideline on thiopurines recommends both TPMT and NUDT genotyping (Koutsilieri et al, 2019;Relling et al, 2019).…”
Section: Genetic Variances and Toxicitymentioning
confidence: 99%